Fresno County Economic Opportunities Commission 20 Year Anniversary Dinner; Julian Bond Keynote Speaker - Watkins, Howard::::::::: (1985)
Keynote speaker Julian Bond at microphone; seated Luisa Medina, Dan Pessano, Joe Williams and Roger Palomino Julian Bond hand out to his right